Genre Realized in Theme: The Case of News Reports and Commentaries - Julia Lavid; Jorge Arús; Lara Moratón (Discours)
The purpose of this paper is to analyze how the clausal thematic features observed in two newspaper genres —news reports and commentaries— can be interpreted as textual signals of their different generic characterization. This is done through the qualitative and quantitative analysis of a sample consisting of thirty-three English texts, divided into two groups of seventeen news reports and sixteen commentaries, respectively. The analysis focused on the following thematic features: (1) the experiential elements selected as Thematic Heads; (2) the semantic nature of the nominal elements realizing these Heads and their internal structure; (3) the textual and interpersonal thematic choices as part of a multiple theme. The analysis reveals that each newspaper genre prefers certain thematic features and that the differences between the two genres are statistically significant. It is suggested that these thematic preferences can be attributed to genre-related variables such as the communicative purpose or the subject matter of the text.